Current collector-free independent battery railway vehicle - Harraz Irfan, Nazaruddin; Mohd Razali, Daud (2021)
Normal electric trains require external electrical infrastructure to obtain power supply. Battery trains (BEMU) has on-board batteries to supply power independently. Battery trains (BEMU) requires external charging infrastructure to charge their batteries when empty. Hence, it is generally very costly to operate electric trains.